Atividades antinociceptiva e antiinflamatória da lectina da alga marinha vermelha Pterocladiella capilacea (S.G. Gmelin) Santelices & Hommersand - Silva, Luana Maria Castelo Melo (2008)
Marine algae lectins had been showing important biotechnical tools. Our objectives were to study the antinociceptive and anti-inflammatory activities of the lectin from the marine red alga Pterocladiella capillacea (Pc). The Pc, presenting haemagglutinating activity against trypsin-treated erytrocytes from rabbit, was purified by application of crude extract (0.025 M Tris-HCl buffer, pH 7.5) on ion exchange chromatography on DEAE-cellulose followed by affinity chromatography on guar-gum column. To proceed, it was used in the nocicepção and inflammation assays, using male Swiss mice and male Wistar rats, respectively. Pc (0.9; 8.1 or 72.9 mg/kg; i.v) it was administered 30 min before each challenge, that is, before the injection i.p of acetic acid 0.8% (10 μl/mL), of the intraplantar injection of 1% formalin (20 μL/paw) or of the Hot Plate test (52±1 ºC), and compared to non treated animals or to pre-treated by Indomethacin or Morphine, both at 5 mg/kg; s.c. It was observed that the Pc (0.9; 8.1 or 72.9 mg/kg) reduced significantly the number of writhes induced by acetic acid (29.2%; 39.3%, and 51.9%, respectively). Pc (72.9 mg/kg) also reduced (p<0.05) the 1st phase (neurogenic) and the 2nd phase (inflammatory) observed after administration of the formalin (58% and 87%, respectively). However, the Pc (72.9 mg/kg) was not capable to reduce the nociception evaluated by Hot Plate test, compared to morphine. These antinociceptive effects were abolished when the Pc was pre-incubated with mucin (1.25 mg/mL), inhibitory glycoprotein of its haemagglutinating activity. Therefore, it is suggested that the antinociceptive activity of the Pc can be predominant by inhibition of peripheric mechanisms. After this, was realized the assays of neutrophil migration for peritoneal cavity or of the paw edema of mice by Carragenan (Cg-type l; 500 g/cavity or paw), where was observed that the administration of the Pc (8,1 mg/kg) 30 min before Cg reduced the neutrophil counts significantly by 84%. However, Pc was not capable to prevent the paw edema induced by Cg. This way, it is suggested that this protein was capable to reduce neutrophil migration by previous mechanism to migration, possibly linking to cellular specific molecules as, for example, selectins. Then, to confirm its safety, the Pc (8.1 mg/kg) was administered daily in mice and observed their behaviors, and at the 7th day, sanguine samples were collected for urea and transaminases (TGO and TGP) dosages, and heavy kidneys and liver. It was observed that Pc did not cause significant alterations, suggesting be safety for the administration period. Considering the data together, it is ended that the Pc possesses antinociceptive and anti-inflammatory properties with peripheral action.